Summer net community production in the northern Chukchi Sea: Comparison between 2017 and 2020 - Kwon, Soyeon; Lee, Inhee; Park, Keyhong; Cho, Kyoung-Ho; Jung, Jinyoung; Park, Taewook; Lee, Youngju; Jeon, Chanhyung; Seo, Seongbong; Hahm, Doshik (Frontiers in Marine Science, 2022)
The Arctic Ocean environment is drastically changing because of global warming. Although warming-induced processes, such as the decrease in sea-ice extent and freshening of the surface layer, have the potential to alter primary production, the changes that will likely occur in their production and their mechanisms are still poorly understood. To assess the potential changes in net community production, which is a measure of biological carbon pump, in response to climate change, we observed the O2/Ar at the surface of the northern Chukchi Sea in the summers of 2017 and 2020. The net community production (NCP) estimates that we derived from O2/Ar measurements were largely in the range of 1 – 11 mmol O2 m-2 d-1 in the northern Chukchi and Beaufort Seas, close to the lower bounds of the values in the global oceans. The average NCP of 1.5 ± 1.7 mmol O2 m-2 d-1 in 2020 was substantially lower than 7.1 ± 7.4 mmol O2 m-2 d-1 in 2017, with the most pronounced decrease occurring in the ice-free region of the northern Chukchi Sea; the NCP of the ice-free region in 2020 was only 12% of that in 2017. The decrease in NCP in 2020 was accompanied by a lower salinity of > 2, which resulted in shallower mixed layer depths and stronger stratification. We speculated that the anomalously low pressure near the east Russian coast and the lack of strong winds contributed to the strong stratification in 2020. With a continuing decrease in the extent of sea ice, the northern Chukchi Sea will likely experience earlier phytoplankton blooms and nitrate exhaustion. Unless winds blow strong enough to break the stratification, the biological pump in late summer is likely to remain weak.